Strategy for Fabricating Tree-Like Branched Al-Al₂Cu Heterogeneous Nanostructures for Future Application in Battery Anodes - Chochoľaková, Elena; Bajtošová, Lucia; Štaffenová, Nikoleta; Hanuš, Jan; Minárik, Peter; Cieslar, Miroslav (Manufacturing Technology Journal, 2025)
Tree-like branched Al-Al₂Cu heterogeneous nanostructures with a high surface area ratio were successfully fabricated using magnetron sputtering of Al matrix and Cu nanoparticles, followed by in situ annealing. The method enables precise control over the composition and morphology of the nanosized columnar Al₂Cu phase grown on the substrate and embedded in the Al matrix. The formation of Al₂Cu begins at the initial locations of sputtered Cu nanoparticles. Further annealing promotes their coalescence and coarsening. Orientation relationships examined in several Al₂Cu particles revealed a semi-coherency with the Al matrix. The high surface area and tunable composition highlight the potential of these nanostructures for advanced battery anodes, with tailored geometry achieved through controlled processing conditions.
Keywords: Al-Al₂Cu nanostructures; Magnetron sputtering; In situ TEM annealing